Steroids for Chronic Inflammatory Demyelinating Polyneuropathy - J Gordon Millichap (Pediatric Neurology Briefs)
The efficacy and safety of high-dose, intermittent IV methylprednisolone (IVMP) as initial and long-term maintenance therapy for chronic inflammatory demyelinating polyneuropathy (CIDP) were analyzed by a retrospective review of outcome data derived from patients’ medical records between 1992 and 2003 at Washington University School of Medicine, St Louis, MO.